Healthy Systems for Universal Health Coverage : A Joint Vision for Healthy Lives - UHC2030 (Geneva: World Health Organization and the World Bank, 2018)
This paper proposes a joint vision for health systems strengthening (HSS) toachieve universal health coverage (UHC). It is intended to be a key referencedocument for the International Health Partnership for UHC 2030 (UHC2030),as well as a broader resource for the global community to inform collaborationon the HSS and UHC agenda. The vision outlines health system performance dimensions and policy entry points to promote UHC through HSS, including critical action for the way forward and principles to guide action.